Integrasi Pendidikan Keagamaan Untuk Pembentukan Karakter di Sekolah Dasar Multikultural - Wahyuni, Neneng Sri; Hidayatuloh, Abdul Aziz; Hasan, Muhammad; Nugraha, Lukman; Rahman, Haedar (Penerbit Widina, Widina Media Utama, 2025)
This study aims to explore the role of integrating religious education into the elementary school curriculum in shaping students' moral, social, and spiritual values. Using a qualitative approach and a case study design at SDN Cigumelor, data were collected through interviews, observations, and curriculum document analysis. The findings indicate that the integration of religious values fosters students' character development—such as empathy, tolerance, discipline, and responsibility—while also creating an inclusive and harmonious classroom environment. This study provides practical contributions to the development of character-based curricula and offers theoretical insights into the importance of religious education in multicultural school settings.ABSTRAKPenelitian ini bertujuan mengeksplorasi peran integrasi pendidikan keagamaan dalam kurikulum sekolah dasar terhadap pembentukan nilai moral, sosial, dan spiritual siswa. Dengan pendekatan kualitatif dan desain studi kasus di SDN Cigumelor, data dikumpulkan melalui wawancara, observasi, dan analisis dokumen. Temuan menunjukkan bahwa integrasi nilai-nilai keagamaan mendorong perkembangan karakter siswa, seperti empati, toleransi, disiplin, dan tanggung jawab, sekaligus menciptakan suasana kelas yang inklusif dan harmonis. Studi ini berkontribusi secara praktis dalam pengembangan kurikulum berbasis karakter serta menawarkan perspektif teoretis tentang pentingnya pendidikan keagamaan dalam lingkungan sekolah multikultural.